PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KEPUASAN KERJA (STUDI PADA RSUD KABUPATEN KONAWE KEPULAUAN - Muhammad Farih; Endro Sukotjo; La Ode Bahana Adam (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The purpose of this study is to explain the influence of the Work Environment and Organizational Culture on Employee Performance Mediated by Job Satisfaction. The research approach used was a survey method, data collection was carried out using an instrument in the form of a questionnaire. The study population was all 60 people of the Konawe Kepulauan District Hospital, because the population was relatively small, all of the population became respondents. The analytical tool used in testing the hypothesis is Partial Least Square (PLS)The results of this study indicate that the work environment has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, the work environment has a positive and significant effect on employee performance, organizational culture has a positive but not significant effect on employee performance, and job satisfaction. positive and significant effect on employee performance. Thus job satisfaction mediates the influence of the work environment and organizational culture on employee performance.